2020
DOI: 10.1186/s13054-020-03326-2
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations for hemodynamic monitoring for critically ill children—expert consensus statement issued by the cardiovascular dynamics section of the European Society of Paediatric and Neonatal Intensive Care (ESPNIC)

Abstract: Background Cardiovascular instability is common in critically ill children. There is a scarcity of published high-quality studies to develop meaningful evidence-based hemodynamic monitoring guidelines and hence, with the exception of management of shock, currently there are no published guidelines for hemodynamic monitoring in children. The European Society of Paediatric and Neonatal Intensive Care (ESPNIC) Cardiovascular Dynamics section aimed to provide expert consensus recommendations on hemodynamic monitor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 77 publications
0
33
0
Order By: Relevance
“…Only recently investigators have reported on the mathematical conversions to allow comparison of NIRS data between devices ( 74 , 75 ). Due to these limitations, the European Society of Paediatric and Neonatal Intensive Care recommends against routine clinical use of NIRS in all children with hemodynamic instability and there is no agreement from the group on the significance of a decline in ScO 2 from baseline or a lower limit of normal ( 76 ).…”
Section: Fetal and Neonatal Cbf Monitoring Techniquesmentioning
confidence: 99%
“…Only recently investigators have reported on the mathematical conversions to allow comparison of NIRS data between devices ( 74 , 75 ). Due to these limitations, the European Society of Paediatric and Neonatal Intensive Care recommends against routine clinical use of NIRS in all children with hemodynamic instability and there is no agreement from the group on the significance of a decline in ScO 2 from baseline or a lower limit of normal ( 76 ).…”
Section: Fetal and Neonatal Cbf Monitoring Techniquesmentioning
confidence: 99%
“…This is in conjunction with current guidelines and studies ( 11 , 21 ) although 20 ml/kg is still used by some. Fluid therapy was guided most frequently by clinical signs and symptoms, although research has shown that these do not always predict fluid responsiveness in a reliably way ( 22 , 23 ). Fluid responsiveness, defined as an increase in cardiac output as a result of fluid loading, was sometimes determined using various methods.…”
Section: Discussionmentioning
confidence: 99%
“…This can be a result of the sparse use of invasive tools for hemodynamic monitoring, such as central venous pressure or pulmonary artery catheters, in children as compared to adults. Therefore, in contrast to the adult ICU, fluid resuscitation is not always performed based upon valid parameters and might contribute to fluid overload ( 23 , 24 ). Future research needs to identify more accurate parameters for guiding fluid resuscitation in critically ill children in order to prevent fluid overload.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CVP is dependent on several factors, such as venous return, right heart function, and mechanical ventilator settings, and thus does not reliably reflect either preload of the heart or volume status. A lower intravascular volume, as reflected by a lower GEDVi and SV, may thus be accompanied by a lower, equal, or even raised CVP (40). To compensate for reduced intravascular volume, the animals with the restrictive regimen had higher heart rates, suggesting they were slightly lower positioned on the Starling curve than animals receiving liberal fluid.…”
Section: Hemodynamic Resuscitationmentioning
confidence: 99%